Safety of non‐steroidal anti‐inflammatory drugs in postpartum period in women with hypertensive disorders of pregnancy: systematic review and meta‐analysis. (1st September 2020) - Bellos, I.; Pergialiotis, V.; Antsaklis, A.; Loutradis, D.; Daskalakis, G.
ABSTRACT: Objective: To assess the effect of non‐steroidal anti‐inflammatory drugs (NSAIDs) on blood pressure when administered for postpartum analgesia in women with hypertensive disorders of pregnancy. Methods: MEDLINE, Scopus, CENTRAL, Clinicaltrials.gov and Google Scholar databases were searched systematically from inception to 5 December 2019 for studies evaluating the safety of postpartum NSAIDs in women with any gestational hypertensive disorder. Randomized controlled trials (RCTs) and cohort studies were eligible for inclusion. Case–control studies, case series and case reports were excluded. The primary outcomes of interest were the incidence of severe hypertension and systolic, diastolic and mean arterial blood pressure. Pooled estimates were obtained by fitting a random‐effects statistical model. The quality of evidence was assessed according to Grading of Recommendations, Assessment, Development and Evaluations (GRADE) guidelines. Results: Ten studies were included, comprising five RCTs and five retrospective cohort studies and involving a total of 1647 women. All studies were evaluated qualitatively and eight of them were included in the quantitative meta‐analysis. Administration of NSAIDs was not associated with a significantly higher risk of severe postpartum hypertension (odds ratio, 1.52 (95% CI, 0.77–3.01)). Similarly, no significant differences were found in postpartum systolic blood pressure (mean difference (MD), –3.03 mmHg (95% CI, –6.21 to 0.15 mmHg)) and mean arterial pressure (MD, –0.38 mmHg (95% CI, –1.88 to 1.11 mmHg)) between women who received NSAIDs and those who did not, whereas postpartum diastolic blood pressure was marginally lower in women treated with NSAIDs (MD, –2.28 mmHg (95% CI, –4.44 to –0.13 mmHg)). The same effects were observed when studies with a large sample size, RCTs, women with severe pre‐eclampsia and studies using ibuprofen as the study drug and acetaminophen as the control treatment were examined separately. The credibility of evidence was judged to be very low according to GRADE, owing to concerns about study limitations, inconsistency and imprecision. Conclusions: This meta‐analysis suggests that postpartum administration of NSAIDs is not associated with elevated blood pressure in women with hypertensive disorders of pregnancy. However, the existing evidence is of very low quality, thus future large‐scale RCTs are warranted to verify the safety of postpartum NSAIDs in this population. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.